2010
DOI: 10.1002/marc.200900869
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Ligand‐Containing Polymers: Terpyridine as the Supramolecular Unit

Abstract: New and interesting properties can be obtained from macromolecular architectures functionalized with supramolecular moieties, particularly metal-ligand complexes. Self-assembly, based on the selective control of noncovalent interactions, guides the creation of hierarchically ordered materials providing access to novel structures and new properties. This field has expanded significantly in the last two decades, and one of the most ubiquitous functionalities is terpyridine. Despite its wide-spread use, much basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
118
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(122 citation statements)
references
References 73 publications
4
118
0
Order By: Relevance
“…This metal was chosen because of its well-documented preference to adopt an octahedral coordination geometry and its ability to form either 1:1 or 2:1 complexes with terpy ligands. [7] In agreement with the literature data, [8] the 1 H NMR spectra taken in CDCl 3 /CD 3 OD (6:4) showed that T(C6) forms either the 1:1 or the 1:2 Zn/T(C6) complex, depending on the ratio between the analytes used and that these complexes are in slow exchange on the NMR time scale (Figure 1). …”
Section: Resultssupporting
confidence: 80%
“…This metal was chosen because of its well-documented preference to adopt an octahedral coordination geometry and its ability to form either 1:1 or 2:1 complexes with terpy ligands. [7] In agreement with the literature data, [8] the 1 H NMR spectra taken in CDCl 3 /CD 3 OD (6:4) showed that T(C6) forms either the 1:1 or the 1:2 Zn/T(C6) complex, depending on the ratio between the analytes used and that these complexes are in slow exchange on the NMR time scale (Figure 1). …”
Section: Resultssupporting
confidence: 80%
“…In addition to solvent components, the octahedrally coordinated zinc ion binds a maximum of two tridentate ligand molecules, thereby forming the bis-complex Zn(tpyNO) 2 . Zn(tpyNO) is the mono-complex and, together with tpyNO, resembles the monomeric state, while the bis-complex resembles the dimer.Metal-tpy complexes have been widely studied in the field of supramolecular chemistry using both dia-and paramagnetic metal ions, [11][12][13][14][15] and have also been of interest in EPR spectroscopy for the determination of nitroxide-nitroxide and metalnitroxide distance measurements. 16 While paramagnetic metal ions could allow measuring the metal-nitroxide distance, 16 here, we chose the diamagnetic Zn(II) as it does not shorten relaxation times of the tpyNO ligands by paramagnetic relaxation enhancement.…”
mentioning
confidence: 99%
“…These crucial parameters have re-enforced the systematic effects of the redox state on coordinative interactions observed by direct comparison of forces (Fig. 4e) 40,41 . On the one hand, the discrepancy could be in part owing to high uncertainty in the estimates of parameter k on by AFM, as also noted by previous reports on other systems [34][35][36][37] .…”
Section: Resultsmentioning
confidence: 92%